A photopaper‐based low‐cost, wideband wearable antenna for wireless body area network applications. Issue 15 (29th October 2022) - Jabbar, Abdul; Zubair, Muhammad; Naveed, Muhammad Ashar; Mehmood, Muhammad Qasim; Massoud, Yehia
Abstract: This study presents a low‐cost, compact, flexible, and wideband wearable antenna for different wireless body area network (WBAN) band applications, covering medical body area network band of 2.4 GHz, industrial, scientific, and medical band of 2.45 GHz, WiMAX band of 3.5 GHz, and wireless local area network band of 5.2 GHz. The final antenna topology is obtained by hexagonal microstrip radiator patch fabricated on commercially available low‐cost photo paper substrate and defected ground plane below the feed line acting as a partial ground to achieve a conformable structure wideband operation. The overall size of the fabricated antenna is 30 × 40 mm 2 and yields a wide‐bandwidth of 3 GHz (2.30–5.30 GHz), radiation efficiency of 84.35%, and the highest gain of 3.48 dBi at the centre frequency of 5.2 GHz, and minimum gain of 1.91 dBi at 2.45 GHz. Furthermore, our detailed numerical and experimental investigations involving specific absorption rate performance assessment and bending analysis revealed the proposed design's excellent robustness to both human body loading and structural deformation scenarios. Therefore, simulated and measured results strongly advocate that the proposed design has profound implications for flexible and body‐worn devices in WBAN applications. Abstract : A low‐cost, compact, flexible, and wideband wearable antenna is presented for different wireless body area network (WBAN) band applications, covering medical body area network (MBAN) band of 2.4 GHz, industrial, scientific, and medical (ISM) band of 2.45 GHz, WiMAX band of 3.5 GHz, and wireless local area network (WLAN) band of 5.2 GHz. The final antenna topology is obtained by the combination of hexagonal microstrip radiator patch fabricated on commercially available low‐cost photo paper substrate and defected ground plane below the feed line acting as a partial ground, to achieve a structure conformable wideband operation. The detailed numerical and experimental investigations revealed extremely good robustness to both human body loading and structural deformation, making it an ideal candidate for flexible and body‐worn devices in WBAN applications.